Comparing The Efficacy and Safety of Intrathecal Hyperbaric Ropivacaine and Bupivacaine for Cesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Vandna Arora; Roopa; Suresh Kumar Singhal; Nidhi Bangarwa; Priya (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Ropivacaine is a long-acting amide local anesthetic that is relatively less potent than bupivacaine and has a higher therapeutic index and better safety profile. Hyperbaric ropivacaine prepared by adding glucose to ropivacaine has been used for spinal anesthesia in cesarean section and lower limb surgeries. Objective: Recently with commercially available hyperbaric ropivacaine, the present study aims to compare the efficacy and safety of hyperbaric ropivacaine vs hyperbaric bupivacaine in patients undergoing cesarean section under spinal anesthesia. The primary objective was to compare the onset and duration of sensory and motor block between the two groups. Secondary objectives included comparison of the maximum level of sensory block achieved and frequency of adverse effects. Material and Method: The present prospective, randomized, double-blind study was conducted after institutional ethical clearance. We included 90 pregnant females belonging to American Society of Anesthesiologists class II, scheduled to undergo lower segment cesarean section under spinal anesthesia. Patients were randomized into two groups of 45 each; Group R received 2 mL of intrathecal hyperbaric ropivacaine (0.75%), and Group B received 2 mL of intrathecal hyperbaric bupivacaine (0.5%). A standardized routine protocol was used for anesthesia including the technique of subarachnoid block in all patients. Result and Discussion: Demographic parameters were comparable between the two groups. The onset of sensory block at the T10 level was significantly faster with bupivacaine as compared to ropivacaine (p=0.026). The maximum level of sensory block (T4) achieved was significantly faster in bupivacaine than ropivacaine (p=0.013). The mean duration of analgesia was comparable in both the groups (p=0.58). The mean duration of motor block was significantly shorter with ropivacaine as compared to bupivacaine. The incidence of hypotension and bradycardia was comparable between both the groups. Conclusion: Hyperbaric ropivacaine provides comparable sensory anesthesia with significantly shorter motor block duration compared to bupivacaine, making it a suitable alternative for elective cesarean sections where early ambulation is desired.